Assessing the relationship between corporate governance scores and company performance on JSE - Sebone, Daphney Sebone (My University, 2014)
This study examines the relationship between corporate governance and share returns of those companies listed on the JSE. Additionally this study examines whether companies which score higher in corporate governance perform better than those with lower scores. A sample of 31 Top 40 listed company on the Top 40 index from 2008 to 2012 (a total of 155 firm year observations) was reviewed. Corporate governance data was collected from the selected companies through a corporate governance questionnaire (CGQ). The share prices and other financial data were obtained from McGregor BFA. Different from the previous studies, this study obtained corporate governance data directly from the companies rather than relying on secondary annual integrated reports. The results indicate that the levels of corporate governance in the JSE listed companies are high but substantial differences still exists. The corporate governance scores (CGX) ranged from a minimum of 58% to 91%. The results based on the multiple regression shows that there is a significant positive relationship between corporate governance and share returns. Also, the results of the independent sample T-test indicate that companies with a higher CGX have better share returns than those with Low CGX. These findings could mean that market perceives corporate governance as a good practice to reduce the agency problem. Three of the control variables included were found to have a significant negative effect on the share returns. These include Book to market value (BM), Company risk (STDDEV), and Dividend Yield (DY). The results conclusively indicate that corporate governance has an effect on share returns.
Keywords: Johannesburg Stock Exchange , Corporate governance , Stocks -- Prices -- South Africa